ANALISIS KASUS PEMBUNUHAN BERENCANA DI SUMBA BARAT DAYA - Samara, Finsensius; Rabawati, Dwytias Witarti; Temaluru, Thermuthis; R. Y. Ego, Melkior; J. Ulumando, Jainudin; A. Saba, Excel (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The crime of premeditated murder is a serious crime that has a major impact on the victim, family and society. This study discusses the premeditated murder case that occurred on August 18 2021 in Kahele Ghura Village, Kadu Eta Village, North Kodi District, Southwest Sumba Regency. This case involved three perpetrators, namely Robertus Rangga Mone, Petus Pati Mone (DPO), and Daniel Rangga Wonda (DPO), with the victim named Hermanus Rehi Tebe Kati. Based on legal analysis, the perpetrators' actions fulfilled the elements of the crime of premeditated murder as regulated in Article 340 of the Criminal Code, namely that they were carried out intentionally, accompanied by prior planning, and caused the death of the victim. This study also evaluates the process of inquiry, investigation and preparation of indictments by the Public Prosecutor (JPU). The legal process carried out is in accordance with the Criminal Procedure Code, where the determination of suspects is based on valid evidence, such as witness statements, evidence and post-mortem results. Judges in deciding cases consider juridical aspects, including the prosecutor's indictment and evidence, as well as non-juridical aspects, such as the motive of the perpetrator and the social impact of the case.